6
$\begingroup$

Consider a function $f(x) = x^4+x^3+x^2+x+1$, where x is an integer, $x\gt 1$. What will be the remainder when $f(x^5)$ is divided by $f(x)$ ?

$f(x)=x^4+x^3+x^2+x+1$

$f(x^5)=x^{20}+x^{15}+x^{10}+x^5+1$

$\endgroup$
0

4 Answers 4

11
$\begingroup$

Rewrite the expression as $$(x^{20}-1) +(x^{15}-1)+(x^{10}-1)+(x^5-1)+1+4.$$ The expression $x^4+x^3+x^2+x+1$ divides the first four terms, since $x^5-1$ does. So the remainder is $5$.

The idea obviously generalizes.

$\endgroup$
2
  • $\begingroup$ Nice solution André Nicolas..... $\endgroup$
    – juantheron
    Dec 31, 2013 at 4:30
  • $\begingroup$ can some one please explain this solution a little bit more as I am not able to understand it properly. $\endgroup$
    – Ganit
    Sep 6, 2021 at 8:46
4
$\begingroup$

Let $x^{20}+x^{15}+x^{10}+x^5+1=(x^4+x^3+x^2+x+1)Q(x)+R(x)$.

$x^4+x^3+x^2+x+1=0$ has $4$ complex roots $a_1,a_2,a_3,a_4$. And these are also roots of $x^5=1$, so when $x=a1,a2,a3,a4$, the above equation becomes

$5=R(a_i)$ ($i=1,2,3,4$)

This is true when $R(x)=5$ for every $x$, and it is easy to show that a polynomial of degree $3$ like this is unique. So the remainder is just $5$ (constant).

$\endgroup$
0
2
$\begingroup$

Observe that $f(x^5) = f(x)(x^{16}-x^{15}+2x^{11}-2x^{10}+3x^6-3x^5+4x-4) + 5$.

So the remainder will be $5$.

$\endgroup$
1
$\begingroup$

$f_1(x)=x+1$

$f_1(x^5)=x^5+1$

$f_1(x^5)$, when divided by $f_1(x)$ leaves a remainder 0.

$f_2(x)=x^2+x+1$

$f_2(x^5)=x^{10}+x^5+1$

$f_2(x^5)$, when divided by $f_2(x)$ leaves a remainder 0.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.